Autocidal gravid ovitraps protect humans from chikungunya virus infection by reducing Aedes aegypti mosquito populations. - Tyler M Sharp; Olga Lorenzi; Brenda Torres-Velásquez; Veronica Acevedo; Janice Pérez-Padilla; Aidsa Rivera; Jorge Muñoz-Jordán; Harold S Margolis; Stephen H Waterman; Brad J Biggerstaff; Gabriela Paz-Bailey; Roberto Barrera (Public Library of Science (PLoS), 2019)
Background Public health responses to outbreaks of dengue, chikungunya, and Zika virus have been stymied by the inability to control the primary vector, Aedes aegypti mosquitos. Consequently, the need for novel approaches to Aedes vector control is urgent. Placement of three autocidal gravid ovitraps (AGO traps) in ~85% of homes in a community was previously shown to sustainably reduce the density of female Ae. aegypti by >80%. Following the introduction of chikungunya virus (CHIKV) to Puerto Rico, we conducted a seroprevalence survey to estimate the prevalence of CHIKV infection in communities with and without AGO traps and evaluate their effect on reducing CHIKV transmission. Methods and findings Multivariate models that calculated adjusted prevalence ratios (aPR) showed that among 175 and 152 residents of communities with and without AGO traps, respectively, an estimated 26.1% and 43.8% had been infected with CHIKV (aPR = 0.50, 95% CI: 0.37-0.91). After stratification by time spent in their community, protection from CHIKV infection was strongest among residents who reported spending many or all weekly daytime hours in their community:10.3% seropositive in communities with AGO traps vs. 48.7% in communities without (PR = 0.21, 95% CI: 0.11-0.41). The age-adjusted rate of fever with arthralgia attributable to CHIKV infection was 58% (95% CI: 46-66%). The monthly number of CHIKV-infected mosquitos and symptomatic residents were diminished in communities with AGO traps compared to those without. Conclusions These findings indicate that AGO traps are an effective tool that protects humans from infection with a virus transmitted by Ae. aegypti mosquitos. Future studies should evaluate their protective effectiveness in large, urban communities.